NUMERICAL DIRECTIONAL OVERCURRENT PROTECTION FOR POWER DISTRIBUTION NETWORK - AHMAD, MUHAMMAD NURULDIN (Universiti Teknologi PETRONAS, 2007)
The studypropose the use of symmetrical-phase-sequence which combine both fault direction and inverse time response characteristics of overcurrent protection in determiningfault direction with high sensitivity in parallel transmission lines. Nondirectional overcurrent protection systemsfail to discriminate thefault for the relay co-ordination whenfault current canflows in eitherforward or reverse directions. In the other hands, analogue overcurrent protection system has many weaknessessuch as very low reliability, inaccurate, inconsistence, and slow response which can be encountered by using digital technique. Meanwhilefor the single transmission lines models, there are still severalflaws that can befound, like if a fault occurred in the middle of transmission line and in the same time one of the generator facing a problem, certain busbar that supplied to the load will lost itsfunction. The scheme used is basedon the symmetrical-phase-sequence components which consist ofzerophase sequence, positive-phase sequence, andnegative-phase sequence. Some studies have been made to identify several types offaults related to the systems proposed. Every protection systems have three basic components: instrument transformers, relays and circuit breakers. Generally, the currents and voltages of eachphase are convertedfrom analogue to digital signal by data acquisition system (DAS), which located inside digital directional overcurrent relay. The concept to be employed to perform digital directional overcurrent protection system is discussed in this report. The future work to be done is to do simulation in order toprove that the algorithm proposed is applicable to perform the digital directional overcurrent protection for theparallel-line distribution network.